Pelatihan Guru Dalam Kegiatan Pembuatan Rencana Pelaksanaan Pembelajaran (RPP) Merdeka Belajar di MI NU Raman Agung Kecamatan Buay Madang Timur - Rodin, Imam; Pravitasari, Dyah (Jurnal Indonesia Mengabdi, 2020)
This activity is motivated by the importance of understanding the making of a learning implementation plan. In fact, many teachers do not make lesson plans when they are going to carry out learning, this is because in making lesson plans must fulfill several very detailed components so that time in preparing the process of learning and evaluation activities is reduced. With the new regulation issued by the Ministry of Education and Culture regarding the "independent learning" policy, it states that simplifying the lesson plans will ease the administrative burden on teachers, as for the core components in the lesson plans, namely learning objectives, learning steps and assessment. The purpose of this activity is to provide training and present some materials related to independent learning and how to make RPP with the latest format. The methods used in this activity were lectures, question and answer discussions and the practice of making lesson plans with the latest format. The result of this dedication is that the training participants are very enthusiastic when the training is ongoing, the teachers can understand the concept of independent learning, are able to make lesson plans with the latest format, and are motivated to make lesson plans because there are only a few components in it.